Trunk stability, trunk strength and sport performance level in judo - Barbado, D.; Lopez-Valenciano, A.; Juan-Recio, C.; Montero-Carretero, C.; van Dieën, J. H.; Vera-Garcia, F.-J. (PLOS ONE, 2016)
Although trunk muscle function has been suggested to be a determinant of judo performance, its contribution to high-level performance in this sport has been poorly studied. Therefore, several tests were used to assess the differences in trunk muscle function between 11 international and 14 national level judo practitioners (judokas). Trunk strength and endurance were assessed using isokinetic tests and core stability was assessed using two protocols: 1) sudden loading, to assess trunk responses to unexpected external perturbations; 2) stable and unstable sitting, to assess the participants` ability to control trunk balance. No differences between groups were found for trunk flexor isokinetic strength, trunk responses against lateral and posterior loading and trunk control while sitting. However, international level judokas showed significantly higher trunk extensor isokinetic strength (p <0.05) and lower trunk angular displacement after anterior trunk loading (p <0.05) than national level judokas. Few and low (r < 0.512) significant correlations were found between strength, endurance and stability parameters, which suggests that trunk strength and endurance are not limiting factors for trunk stability in competitive judokas. These results support the importance of trunk extensor strength and trunk stability against forward perturbations in elite judo performance.